The Influence of Vertebral Fracture on the Functional Disability of Patients with Rheumatoid Arthritis - Cho, Soo-Kyung; Lee, Joo-Hyun; Han, Minkyung; Lee, Seunghun; Kim, Ji Young; Ryu, Jeong Ah; Choi, Yun Young; Bae, Sang-Cheol; Sung, Yoon-Kyoung (Journal of Korean medical science, 2014)
The aim of the present study was to identify the influence of vertebral fracture (VF) on the functional disability in patients with rheumatoid arthritis (RA). This study consecutively enrolled 100 female patients aged 50 yr or older with RA. All participants underwent lateral imaging of the thoracolumbar spine by simple radiography to identify any VFs. They also completed questionnaires via interview regarding demographics, medical history, and disease outcomes including functional disability. We used univariate analysis to evaluate associations between functional disability and VF, and made multivariate logistic regression models to test independent effect of the presence of VF, the number of VFs, and the severity of VF on functional disability. Among the 100 RA patients, 47 had at least one VF, but 34 of them were asymptomatic that they had experienced a fracture. The multiple VFs ≥ 3 (OR, 8.95; 95% CI, 1.77-44.15, P = 0.01) and moderate or severe VF (OR, 3.38; 95% CI, 1.26-9.04, P = 0.02) were related to disability in univariate analysis. The multiple VFs ≥ 3 (OR, 6.13; 95% CI, 1.02-36.94, P = 0.048) was associated with functional disability of RA patients after adjusting various confounders and it was mainly in walking and arising. The VF might be an important factor which affects functional disability in RA patients.